Analysis of Distance On Ground Vibration at Around Residential Areas in PT Semen Padang Indarung West Sumatera Province - Muhammad Rizki Aulia; Irvani Irvani; Haslen Oktarianty (MINERAL, 2020)
One of the blasting activity impact in Exsisting Pit by PT Semen Padang is producing the ground vibration. Analyzing the blasting distance needed to know the level of ground vibration. From that analysis, the actual value and prediction value of Peak Vector Sum (PVS) and value of vibration by SNI 7571 : 2010. The measuring of ground vibration level is done in Mess APN as residents settlement, wich is located as far as 611 meters from blasting location. The measurement starts by measuring the blasting geometry, the amount of drill hole, blasting distance, and ground vibration for about 13 data. Those data are processed using Shotplus-I to make the blasting design and the ground vibration level will be known by using blastmate. From the 13 data of ground vibration Mess APN that known on the distance 464 m the result of ground vibration is 1.651 mm/s while on the distance 478 the result of ground vibration is 2.382. Based on the result that can be seen there is an anomaly data, that caused the same blasting geometry treatment for rock structure on mine site. Beside, according measurement data wich are measured in Mess APN, the average value of ground vibration is 1.511 mm/s. It show that the ground ground vibration does not cause a significant impact in Mess APN as residents settlement and does not exceed the limit value of class 2 building category by SNI 7571:2010 (limit value is 3 mm/s)